Manajemen Mutu dan Kesiapan UMKM Alas Kaki/Kulit dan Konveksi Bogor Menghadapi Masyarakat Ekonomi ASEAN 2015 - nazlifah, siti; cahyadi, eko ruddy; andrianto, m syaefudin (IPB University, 2016)
The implementation of the ASEAN Economic Community (AEC) requires Bogor footwear/leather and convection Small Medium Enterprises (SMEs) meet the market’s standards and needs. The research aims to identify the characteristics of SMEs and the quality perception of quality management system, analyze the readiness of SMEs to face the AEC and the influence of the quality management system on the readiness of SMEs to face the AEC. The data from Bogor SMEs sevices used, then followed by snowball sampling method. The data analyses used are descriptive analysis, T-test and logistic regression analysis. The result showed that convection SMEs compare to footwear/leather SMEs is more prepared in general, marketing and production/operation aspects. Educational level of business owner and the legal entity significantly affect the SMEs readiness facing AEC. The business owners have not implemented the quality management well, especially on the principle of system approach to management and the facts-based decision making, although these two principles are significantly affect the readiness of SMEs to face AEC 2015.